DNA barcoding of Arius species (Siluriformes: Ariidae) found in Peninsular Malaysia waters, using mitochondrial Cytochrome oxidase subunit I gene. - Abdurahman, Siti Waznah; Ambak, Mohd Azmi; Md. Sheriff, Shahreza; Chowdhury, Ahmed Jalal Khan (2014)
Ariid catfishes are widely distributed in tropical and temperate continental shelves all over the world, mainly inhabiting inshore waters and estuarine regions, or in some cases confined to freshwaters. Ariid catfishes, commonly known as the sea catfishes, belong to family Ariidae (order: Siluriformes). Ariids are one of the problematic groups for the identification using their morphological features. Furthermore, keys available for the identification are unclear and confusing. Thus, this study was done in order to determine the species in one of the problematic ariid’s genera, Arius, which found in Peninsular Malaysian waters using molecular approach. There were four species of Arius found in this study, Arius leptonotacanthus, Arius maculatus, Arius oetik and Arius spp. All the species were sequenced for 499-bp region of the mitochondrial cytochrome oxidase subunit I (COI) gene. Five sequences per species were amplified and a neighbour-joining phylogenetic tree using Tamura-3 parameter (T92+G) model was constructed. The results shows that Arius leptonotacanthus formed the base for other Arius species (A.maculatus, A.oetik and Arius spp.) supported by a moderate bootstrap value of 50%. Whereas, Arius maculatus formed a sister taxa to Arius spp. with 91% of bootstrap value. Overall, the phylogenetic tree shows that all the Arius species were grouped in separate clades according to the respective species with the support of high bootstrap values. Thus, this study revealed that this problematic Arius species can be clearly differentiated using the molecular marker.